Sensitization to household allergens in children with bronchial asthma and allergic rhinitis in St. Petersburg - O. V. Trusova; A. V. Kamaev; N. L. Lyashenko; I. V. Makarova; E. A. Stolyarova (Аллергология и Иммунология в Педиатрии)
Local studies of various types of domestic sensitization in patients are in demand and have practical value.Objective: to study the spectrum of domestic sensitization in children with allergic rhinitis (AR) and bronchial asthma (BA) in St. Petersburg, in connection with the main clinical data. Materials and methods. The study included 360 patients with perennial allergies, 216 boys, 144 girls, aged 5 to 17.9 years (mean age 9.13 ± 3.41 years). Skin prick tests on the front surface of the forearm with water-salt extracts (joint stock company Biomed, Russia) were carried out and evaluated according to the standard method with allergens: house dust, D. pteronyssinus, D. farinae, cat, dog, horse, pillow feather. The test was considered positive with a maximum wheal diameter of ≥3 mm 15 min. after application.Results. In the structure of domestic sensitization in children with AR and BA, house dust mite allergens were in the lead; the most common sensitization was to D. farinae (70.3%) and D. pteronyssinus (60.8%), as well as to a cat (54.2%) and a dog (52.8%). In children with moderate asthma, the cat allergen was in the lead, exceeding the level of sensitization to house dust mites. The frequency of sensitization to various allergens increased significantly with the increase in the allergic disease duration.Conclusion. The high significance of house dust mite allergens, as well as epidermal allergens in children with perennial AR and BA, should be taken into account when planning allergological evaluation and treatment measures..